An evaluation of knowledge, attitude and practice of pharmacovigilance among prescribers in a teaching hospital of south India - Shivarudraiah, Prasad R.; Kudthni, Ravi H.; Ramakrishna, Santhosh; Koushik, S. S.; Karki, Prajna V.; Kedia, Radhika (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Adverse drug reactions (ADRs) represent a serious health problem. Effective generation of ADR related data helps in practicing evidence-based medicine and thus prevents many adverse drug reactions. Spontaneous reporting of ADRs has remained the major sources of information of pharmacovigilance. Underreporting of ADRs is a common problem. In order to improve the reporting rate, it is important to improve the Knowledge, Attitude and Practices (KAP) of the prescribers regarding ADR reporting and Pharmacovigilance. Hence this study was undertaken to assess the knowledge, attitude and practice regarding Pharmacovigilance among doctors of Shridevi Institute of Medical Sciences and Research Hospital, Tumkur, Karnataka. Methods: This was a cross sectional, observational, questionnaire based study conducted using a predesigned Knowledge Attitude Practice (KAP) questionnaire among 110 doctors. The completed KAP questionnaire was collected and data analyzed. Results: Most of the doctors (98.15%) accepted that reporting ADR is necessary. 67.31% agreed that ADR reporting is necessary for identifying safety of the drug and 94.44% agreed that pharmacovigilance should be taught in detail to health-care professionals. But there was a huge gap between the ADR experienced (80%), and ADR reported (25.45%) by the prescribers. Only 29.09% medical professionals have ever seen the ADR reporting form and only 16.36% respondents have been trained on reporting on ADR. Conclusions: Study revealed that the majority of the doctors had a good knowledge but poor attitude and practice of pharmacovigilance. They should be trained properly on ADR reporting to improve the current scenario in the pharmacovigilance program of the country.